2024
DOI: 10.1161/jaha.123.032212
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trend in Revascularization for Patients With Ischemic Cardiomyopathy and Multivessel Coronary Artery Disease

Anas H. Alzahrani,
Sundos Alabbadi,
Shinobu Itagaki
et al.

Abstract: Background Current guidelines recommend revascularization in patients with ischemic cardiomyopathy (ICM). However, there is limited information about the trends and outcomes of coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) in ischemic cardiomyopathy patients with multivessel coronary artery disease. Methods and Results Using New Jersey state mandatory registries, 8083 patients with ischemic cardiomyop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Alzahrani et al [ 20 ] reported a temporal trend of surgical and percutaneous revascularization in patients with ischemic cardiomyopathy and multivessel coronary artery disease over 12 years. In terms of patient outcomes, a 30-day mortality rate was higher after PCI versus CABG, though similarity was gained/it was similar for CABG and PCI groups, which included completeness of revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Alzahrani et al [ 20 ] reported a temporal trend of surgical and percutaneous revascularization in patients with ischemic cardiomyopathy and multivessel coronary artery disease over 12 years. In terms of patient outcomes, a 30-day mortality rate was higher after PCI versus CABG, though similarity was gained/it was similar for CABG and PCI groups, which included completeness of revascularization.…”
Section: Discussionmentioning
confidence: 99%